Consequences of False Memories in Eyewitness Testimony: A Review and Implications for Chinese Legal Practice - Wang, Jianqin; Otgaar, Henry; Smeets, Tom; Howe, Mark L.; Merckelbach, Harald; Zhou, Chu (UI Scholars Hub, 2018)
False memories can result in severe legal consequences including the imprisonment of innocent people. False memory in eyewitnesses is the largest factor contributing to miscarriages of justice in the United States. To date, no study has focused on how false memories might play a role in the Chinese legal system. The purpose of this review is to summarize the latest findings on false memory and eyewitness testimony in the literature, and to shed some light on how the Chinese legal system may incorporate these experiences into practice. Overall, false memories of eyewitnesses are generated either by external misleading information or by internal cognitive processes; false memories may guide police investigations in the wrong direction or cause eyewitnesses to misidentify an innocent person as the perpetrator. We conclude that specially designed interview protocols such as the Cognitive Interview, warnings given to eyewitnesses, and blind lineup administration may prevent or lower the risk of false memory occurrence.